2019
DOI: 10.7897/2230-8407.1009268
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Heavy Metals in Different Brands of Amlodipine Besylate Tablet Dosage Forms by Inductively Coupled Plasma-Mass Spectrometry (Icp-Ms)

Abstract: The aim of this study is to estimate heavy metals in different brands of amlodipine besylate tablet dosage forms by inductively coupled plasma-mass spectrometry (ICP-MS). In many laboratories around the world as the instrument of choice for performing trace metal analysis is ICP-MS. ICP-MS using Kinetic Energy Discrimination (KED) mode was used. Samples are assimilated using multi-wave sample digestion system. Each element standards of conc. 1000 mg/l was prepared and followed by serial dilution with 2% nitric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…(five studies) (see Table 4) [30][31][32][33][34], and antihypertensive medicines-amlodipine (seven studies), nifedipine (two studies), methyldopa (three studies), enalapril (three studies) and hydralazine (one study) (see Table 5) [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. No study assessing quality of labetalol was identified.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…(five studies) (see Table 4) [30][31][32][33][34], and antihypertensive medicines-amlodipine (seven studies), nifedipine (two studies), methyldopa (three studies), enalapril (three studies) and hydralazine (one study) (see Table 5) [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. No study assessing quality of labetalol was identified.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…We found 15 studies on the quality of antihypertensives (Table 5) [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. Seven studies evaluated the quality of amlodipine-two studies from India and Nepal found no evidence of poorquality amlodipine [36,38].…”
Section: Antihypertensive Medicinesmentioning
confidence: 99%
See 1 more Smart Citation